Genetic profiling of multidrug-resistant Acinetobacter baumannii from a tertiary care center in Malaysia - Aisyah Syakirah Shahari; Navindra Kumari Palanisamy; Fadzilah Mohd Nor (Microbiology Spectrum)
ABSTRACT Genetic characterization of multidrug-resistant (MDR) Acinetobacter baumannii remains scarce in Malaysia. This study aimed to characterize antibiotic resistance, genomic location, and genetic relatedness among the A. baumannii isolates obtained from a tertiary hospital in Malaysia. A total of 128 MDR A. baumannii isolates were collected from patients admitted to various wards (intensive care unit [ICU], neonatal intensive care unit, coronary care unit, high dependency ward [HDW], and general wards). The isolates were identified by Vitek 2 and PCR amplification of the 16S rRNA gene followed by sequencing. The isolates were tested against imipenem, ceftazidime, amikacin, gentamicin, ampicillin, and ciprofloxacin using disk diffusion, Epsilometer test, and broth microdilution. The antibiotic resistance genes, blaOXA-23, blaOXA-24, blaADC, blaVIM, and blaIMP, were detected in chromosomal and plasmid DNA using PCR. Insertion sequence ISAba1/blaOXA-23 gene was detected on chromosomal DNA only. Isolates with different antibiotic susceptibility patterns and PCR profiles were subjected to multi-locus sequence typing. MDR A. baumannii was predominantly found in HDW (39.84%), general wards (29.69%), and ICU (28.13%). All isolates conferred resistance to carbapenem and more than 90% resistance to the remaining antibiotics. The antibiotic resistance genes blaOXA-23, blaVIM, and blaADC were detected in both chromosomal and plasmid DNA. The ISAba1/blaOXA-23 gene was detected in 99.22% of the isolates. Four sequence types (STs) were distinguished: ST2 (76.67%), ST164 (10%), ST642 (10%), and ST643 (3.33%). ST164 and ST642 were unique and represent a significant finding in Malaysia’s surveillance data. These STs are associated with acquired blaOXA-23, indicating an evolutionary adaptation of A. baumannii within the hospital setting.IMPORTANCEAcinetobacter baumannii is a ubiquitous Gram-negative coccobacillus bacterium that is primarily associated with nosocomial infections that can colonize biotic and abiotic surfaces to enhance cell-to-cell adhesion, ensuring the establishment of infections. To date, the spread of multidrug-resistant A. baumannii (MDRAB) has become rampant and a great concern in the hospital setting, as the available antibiotics are insufficient to treat infections. The antibiotic resistance island resides in a mobile element and rapidly evolved. The antibiotic susceptibility data with its resistance mechanisms would contribute to and facilitate the management and infection control caused by MDRAB.